Importance of the perceived quality of touchpoints for customer journey analysis – evidence from the B2B sector - Christian Koch; Michael Hartmann (Electronic Commerce Research, 2022)
We investigate how the perceived quality influences touchpoint performance to provide a more nuanced understanding for analysing customer journeys. To answer the research questions, a survey in a real life online setting was carried out. The setting contained complex service solutions that were offered in a business-to-business context. The quantitative study shows that the perceived quality of a website has an influence on consumers' buying intention. This correlation increases as the customer journey progresses. The perceived quality influences the website's impact on visitors' buying intention with a medium to strong effect size and the influence of a website's quality on the impact on visitors' buying intention varies significantly at different customer journey phases. While extant research focusses either on customer experience at touchpoints or touchpoints' effects on buying behavior, we combine insights from both streams of research to highlight the role of website quality in determining touchpoint performance along the customer journey. Practitioners can use these insights to allocate resources in marketing and sales more efficiently.
Keywords: 380; Customer journey analysis; Website quality; Online buying intention; Customer journey